Study and valorization of a new bituminous concrete based on natural dune sand for hot and arid environments - Ahmed Berriache; Mohamed Bensoula; Mohamed Zaoui; Tahar Kadri (The Journal of Engineering and Exact Sciences)
The trans-desert road network is exposed to enormous degradation of asphalt concrete pavements due to the high temperatures of these arid regions, which considerably accelerate asphalt ageing. Common bituminous mixes generally use quarry sand fillers, the proportions of which are poorly controlled due to the diversity of rock deposits and their manufacturing conditions. This article responds to this problem by proposing dune sand as a source of filler by grinding it and then introducing it into pure bitumen to obtain the bitumen-filler mix. In this paper, two types of analysis were carried out, one thermal and the other mechanical to study the influence of the substitution of quarry sand filler by dune sand filler in asphalt concrete. In the thermal analysis, the study evaluates the stiffening power (?TBA) of three types of fillers incorporated into a pure bitumen, namely quarry sand, dune sand and standardized filler. The results of these analyses reveal that at a normative percentage of 57% filler with 43% pure bitumen, the stiffening power (?TBA) of dune sand filler and normalized filler comply with established standards (between 8 and 16°C), unlike quarry sand filler, which does not meet standards. The mechanical analysis carried out on quarry sand filler and dune sand filler revealed an improvement in mechanical performance when dune sand filler was used, with MARSHALL stability values indicating an average increase from 3.9 to 4.9, and better resistance to water with a greater than 99% ratio for the DURIEZ test well above the 75% threshold. These results offer the potential to optimize bituminous mixes by incorporating dune sand fillers, thereby enabling Saharan roads to be built more quickly, at lower cost and, above all, to extend their lifespan, making a positive contribution to the development of road infrastructure in hot, arid environments.